2006
DOI: 10.1007/s11222-006-9438-0
|View full text |Cite
|
Sign up to set email alerts
|

DRAM: Efficient adaptive MCMC

Abstract: We propose to combine two quite powerful ideas that have recently appeared in the Markov chain Monte Carlo literature: adaptive Metropolis samplers and delayed rejection. The ergodicity of the resulting non-Markovian sampler is proved, and the efficiency of the combination is demonstrated with various examples. We present situations where the combination outperforms the original methods: adaptation clearly enhances efficiency of the delayed rejection algorithm in cases where good proposal distributions are not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
1,257
0
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,391 publications
(1,265 citation statements)
references
References 16 publications
2
1,257
0
6
Order By: Relevance
“…In this study we rely on Markov chain Monte Carlo techniques, which allow for a Bayesian estimation of parameter distributions and quantify predictive uncertainty through ensemble simulations. Additional information on the algorithms [Haario et al, 2006] can be found in the supporting information S2. Note that trends (both in GRACE and the reconstruction) are removed during model calibration ( Figure S1).…”
Section: Model Identificationmentioning
confidence: 99%
“…In this study we rely on Markov chain Monte Carlo techniques, which allow for a Bayesian estimation of parameter distributions and quantify predictive uncertainty through ensemble simulations. Additional information on the algorithms [Haario et al, 2006] can be found in the supporting information S2. Note that trends (both in GRACE and the reconstruction) are removed during model calibration ( Figure S1).…”
Section: Model Identificationmentioning
confidence: 99%
“…Adding this information will dramatically increase the number of variables on which selection must be made and is likely to make inferring γ more difficult. To address this we will likely require improved proposal distributions for γ , as has been used for continuous variables in Haario et al (2006), which account for the estimated posterior correlations between these latent inclusion parameters. A method to generate correlated binary variables has been proposed in Leisch et al (1988).…”
Section: Future Workmentioning
confidence: 99%
“…For model inference, we used Markov Chain Monte Carlo sampling, where samples were drawn from the posterior distribution using the delayed rejection-adaptive metropolis algorithm. 36 Twenty thousand samples were drawn from each parameter chain, and the 5,000 first samples were discarded as burn-in samples. Figure 3 shows simulation results for a conventional version of the oxygen transport model without incorporating the effect of CTH (panels A-C) (Conv ss model) and a version of the oxygen transport model that includes the effect of CTH (panels D-F) (CTH ss model).…”
Section: Simulations and Data Analysismentioning
confidence: 99%